Perlindungan dan Kesejahteraan Anak dalam Perkawinan di Bawah Umur - Ali Imron (AL-TAHRIR, 2013)
Abstract: A person who will get marriage must meet the administrative and subtantive requirements. These requirements have positive role to echieve the goal and wisdom of marriage for each side. Marriage is permited at the age of 19 years for man and 16 years for woman. Nevertheless the request of dispensation for marriage can be proposed by anyone who needs it because of some reasons. This, of course, would open the opportunity of underage marriage to happen. The dispensation for marriage should be based on the consideration of welfare and goodness of children and family. Even welfare and goodness of children should be put over the interests of parents and family magnitude as a form of the protection of children. Marriage under the age of a regulated- norm of law violates the protection and the welfare of children though they have received legal dispensation from the court . Such marriage would disturb the development of the children’s potential and cause the loss of getting social welfare.